Effect of biaxial strain on electronic and optical properties of GaSe monolayer - Vi, Võ Thị Tuyết; Chương, Nguyễn Văn; Hiếu, Nguyễn Văn; Hiếu, Nguyễn Ngọc (Hue University Journal of Science: Natural Science, 2020)
In this paper, using density functional theory, we systematically investigate the effect of biaxial strain on electronic and optical properties of GaSe two-dimensional layered material with monolayer structure. The calculations indicate that monolayer GaSe is an indirect semiconductor with a bandgap of 1.903 eV at equilibrium. The electronic properties of the GaSe monolayer, especially the bandgap energy, depend strongly on the biaxial strain. The GaSe monolayer has a wide absorption spectrum, from the visible light region to the near-ultraviolet one. Besides, the strain engineering significantly changes the intensity as well as the position of the peaks in the optical spectra of monolayer GaSe.